A functorial model theory : newer applications to algebraic topology, descriptive sets, and computing categories topos - Nourani, Cyrus F (Apple Academic Press, 2014)
This book is an introduction to a functorial model theory based on infinitary language categories. The author introduces the properties and foundation of these categories before developing a model theory for functors starting with a countable fragment of an infinitary language. He also presents a new technique for generating generic models with categories by inventing infinite language categories and functorial model theory. In addition, the book covers string models, limit models, and functorial models.